Stress luminescent film for recording stress information of closed mechanical structure and preparation method of stress luminescent film

The SrAl2O4:Eu2+, Dy3+/polymer stress luminescent film prepared by inorganic-organic simple curing method solves the problems of pre-charge, difficulty in self-recovering of luminescent intensity, and inconvenient monitoring of powder form, and achieves low-threshold stress luminescent and self-recovering luminescent intensity, with good durability and cycling stability.

CN119552507APending Publication Date: 2025-03-04GUIZHOU TIRE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411732643.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

There are three key challenges in actual application of existing stress luminescent materials: pre-charge is required for ultraviolet radiation, the luminescent intensity is difficult to recover, and it is inconvenient to accurately monitor and distribute control in the form of powder.

Method used

A stress luminescent film with the general formula SrAl2O4:Eu2+, Dy3+/polymer was prepared by inorganic-organic simple curing method. A low-threshold stress luminescent film was prepared under low-temperature curing conditions. The material did not require pre-irradiation of high-energy rays to achieve spontaneous recovery of luminescent intensity.

Benefits of technology

Stress luminescence can be achieved by achieving a low threshold, and the stress luminescence intensity can be restored by itself. The material preparation conditions are simple, which are convenient for industrial mass production, and have excellent stress luminescence durability and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552507A_ABST
    Figure CN119552507A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of stress luminescent materials, and discloses a stress luminescent material film for recording stress information of a closed mechanical structure and a preparation method of the stress luminescent material film. The general formula of the stress luminescent material is SrAl2O4: Eu < 2 + >, Dy < 3 + >, the crystal structure belongs to a triclinic system, the activating agent is Eu < 2 + >, and the sensitizing agent is Dy < 3 + > ions. The method comprises the following steps: according to different mass ratios of M1 (SrAl2O4: Eu < 2 + >, Dy < 3 + >): M2 (polymer); the preparation method comprises the following steps: respectively weighing two compound raw materials, uniformly stirring and mixing, pouring into a fixed mold, and carrying out curing treatment in a vacuum environment of a drying oven at the temperature of 80 DEG C for 2 hours to obtain the stress luminescent film. The stress luminescence film can realize stress luminescence without a high threshold, and the stress luminescence intensity of the stress luminescence film can be self-recovered. The method is simple, and mass production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a low-threshold and self-recovering stress luminescent film for recording force information of a closed mechanical structure and a preparation method thereof. Background Art

[0002] At present, there are still deficiencies in the monitoring and understanding of the internal force distribution of machinery, which leads to the equipment often being subjected to unpredictable local stress during operation, which easily causes local stress concentration, and then leads to mechanical fatigue and damage, shortening the service life of the equipment. With the development of science and technology, the demand for mechanical reliability and durability has become more prominent. Therefore, the problem of resource waste caused by mechanical damage has also attracted more attention. It is worth noting that stress luminescent materials can convert the mechanical stress borne by the material into light energy, realize real-time monitoring and visualization of the internal force distribution, and provide innovative means for mechanical design optimization and equipment life extension. In particular, the luminescence intensity of elastic stress luminescent materials has a good linear relationship with the load size, with a low response threshold and good repeatability, and the luminescence intensity can self-recover under certain conditions. It has shown a wide range of application potential in the fields of intelligent electronic signatures, stress sensors and stress display devices.

[0003] However, existing stress luminescent materials still face three key challenges. First, most stress luminescent materials need to be pre-charged by ultraviolet light irradiation. This requirement brings obvious limitations in practical applications and hinders the instant response and irradiation-free operation of the materials. Secondly, after experiencing mechanical stimulation, the luminescence intensity of current stress luminescent materials is difficult to recover to the initial level. Usually, it gradually decays with the accumulation of mechanical stimulation, and eventually loses its luminescence ability and needs to be irradiated again to restore its luminescence effect. This dependence on external irradiation greatly limits its practicality in long-term and multiple application scenarios. Third, most stress luminescent materials exist in powder form, which is not convenient for effective precise monitoring and distribution control in practical applications. Therefore, there is an urgent need to develop a stress luminescent film with low threshold, good elasticity and self-recovery properties to meet the needs of efficient and sustainable stress monitoring and promote its application in the fields of intelligent machinery monitoring and structural health management. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the present invention aims to provide a stress luminescent film that records the stress information of a closed mechanical structure. The present invention adopts an inorganic-organic simple curing method, which has simple preparation conditions and is convenient for mass production. The stress luminescent film of the present invention can achieve stress luminescence at a low threshold, and its stress luminescence intensity can be self-recovering.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A stress luminescent film for recording stress information of a closed mechanical structure, the general formula of which is: SrAl2O4:Eu2+,Dy3+ / polymer:M1 / M2; wherein 1≤M1≤3, 5≤M2≤15, Eu replaces Sr in the crystal; and the activating ion is Eu2+.

[0007] A stress luminescent film for recording stress information of a closed mechanical structure comprises the following steps:

[0008] (1) The general formula is SrAl2O4:Eu2+,Dy3+ / polymer, and the mass ratio of the compounds shown is M1:M2; wherein 1≤M1≤3, 5≤M2≤15; the stress luminescent powder and the polymer raw material are weighed respectively according to the mass ratio.

[0009] (2) The compound raw materials weighed in step (1) are stirred and mixed, poured into a mold, and cured at low temperature, the temperature being 80-120°C.

[0010] (3) Curing the mixture in step (2) at 80-120° C. for 1-4 h in a curing environment to obtain a stress luminescent film that records stress information of a closed mechanical structure with a low threshold.

[0011] The temperature of the low temperature treatment is 80°C.

[0012] The treatment time is 2 hours.

[0013] The curing environment is vacuum.

[0014] The polymer-containing compound raw material is one or more of polydimethylsiloxane, polyurethane, polytetrafluoroethylene and polylactic acid.

[0015] The M1:M2 is preferably 2:10; the low-temperature curing temperature is preferably 80° C., and the curing time is preferably 2 hours for the best luminous effect.

[0016] The stress luminescent material of the present invention is an elastic stress luminescent film.

[0017] The principle of the present invention is as follows: Based on the mechanical stress-induced luminescent center excitation mechanism: when the film is subjected to external mechanical stimulation (compression), the external mechanical energy is effectively converted and transmitted to the stress luminescent powder dispersed in the polydimethylsiloxane matrix, thereby causing the energy level transition of the luminescent center (Eu2+), releasing photons and emitting light. The polydimethylsiloxane matrix provides excellent flexibility and toughness, allowing the film to maintain a stable structure and luminescent performance under repeated mechanical action.

[0018] The stress luminescent film of the present invention can realize stress luminescence at a low threshold, and its stress luminescence intensity can be self-recovered. The stress luminescent film of the present invention has the advantages of simple preparation conditions, batch production, and stable chemical properties, and can be applied to stress sensors, stress distribution imaging and other fields.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0020] (1) Using commercial stress luminescent powder SrAl2O4:Eu2+,Dy3+ and cheap polydimethylsiloxane as the matrix, without using harsh preparation conditions, the low-threshold stress luminescent film is easy to industrialize and mass produce;

[0021] (2) Compared with other existing elastic stress luminescent films, SrAl2O4:Eu2+,Dy3+ / polydimethylsiloxane composite stress luminescent film has unique advantages. It does not require pre-irradiation treatment with high-energy rays and can achieve spontaneous recovery of luminescence intensity under natural light or sunlight. After multiple stress luminescence cycles, the material can still maintain a stable and significant luminescence intensity, showing excellent stress luminescence durability and cycle stability. This feature makes it unnecessary to have additional pretreatment steps in practical applications, thereby reducing operational complexity and cost, and providing an efficient and convenient material choice for reusable stress luminescent enclosed mechanical stress monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the powder X-ray diffraction spectrum of SrAl2O4:Eu2+,Dy3+ of Example 1;

[0023] Figure 2 The stress luminescence spectrum of the ratio (3) SrAl2O4:Eu2+,Dy3+ / polydimethylsiloxane of Example 1 (left); the stress luminescence integral diagram under different forces (with error bars, each mechanical parameter was tested 10 times) (right);

[0024] Figure 3 The actual picture of the bearing stress distribution of the ratio (3) SrAl2O4:Eu2+,Dy3+ / polydimethylsiloxane in Example 1 (left) and the actual picture of stress luminescence under mechanical impact. Figure 4 The mechanical force distribution of the film with ratio (2) in Example 1 inside the bearing. DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive. Below in conjunction with specific embodiments, the present invention will be further described in detail, and for process parameters not particularly noted, conventional techniques may be used.

[0026] SrAl2O4:Eu2+,Dy3+ stress luminescent powder and polydimethylsiloxane were selected as the starting compound raw materials. According to the mass ratio of each compound, there were 4 groups in total, and the ratios were as follows:

[0027] (1) SrAl2O4:Eu2+,Dy3+:polydimethylsiloxane=M1:M2=1g:10g;

[0028] (2) SrAl2O4:Eu2+,Dy3+:polydimethylsiloxane=M1:M2=2g:10g;

[0029] (3) SrAl2O4:Eu2+,Dy3+:polydimethylsiloxane=M1:M2=2g:15g;

[0030] (4) SrAl2O4:Eu2+,Dy3+:polydimethylsiloxane=M1:M2=3g:10g;

[0031] After the mixture is stirred and mixed, it is poured into a mold, and then the mold is placed in an oven and vacuumed. The sample is cured at 80°C for 2h.

[0032] As the oven cools naturally, a stress luminescent film SrAl2O4:Eu2+,Dy3+ / polydimethylsiloxane for recording the stress information of a closed mechanical structure is obtained.

[0033] Figure 1 This is the X-ray diffraction spectrum of the sample SrAl2O4:Eu2+,Dy3+ powder in this embodiment. The spectrum was measured using a Japanese RigakuD / max-IIIA X-ray diffractometer, with a test voltage of 40 kV, a scanning speed of 1.2° / min, a test current of 40 mA, and CuKα1 X-rays with a wavelength of . X-ray diffraction analysis shows that ratio (2) is SrAl2O4 phase, which belongs to the triclinic crystal system.

[0034] Figure 2 The stress luminescence spectrum of the film with the ratio (2) of this embodiment is obtained by using the American Ocean Optics QE65Pro fiber optic spectrometer, with a data acquisition integration time of 600 milliseconds and a scanning step length of 1 nm. Figure 2It can be seen that when the material is subjected to stress (the force is 30N), a stress luminescence peak of about 520nm appears, which corresponds to the energy level transition of Eu2+ ions.

[0035] Figure 3 For the film of ratio (2) in Example 1, the mechanoluminescence spectrum under the action of mechanical force was recorded continuously for 10 times under the condition of each force value of 5-30N (one spectrum was obtained for each force action). The American Ocean Optics QE65Pro fiber optic spectrometer was used, the data acquisition integration time was 600 milliseconds, and the scanning step length was 1nm. The stress luminescence spectrum obtained by 10 consecutive mechanical stimulation cycles was averaged and the error bars were marked to eliminate the errors caused by unstable force. The final results show that as the force gradually increases from 5N to 30N, the stress luminescence intensity gradually increases, and there is a certain linear relationship between its integrated stress luminescence intensity and the force size.

[0036] Figure 4 The mechanical stress distribution of the film with ratio (2) in Example 1 inside the bearing. The experiment embeds the stress luminescent film into the bearing, and uses a self-compiled Matlab program to collect the grayscale value of the stress luminescent signal in real time, so as to monitor the stress distribution inside the bearing intuitively and dynamically. The stress signal is collected using the American Ocean Optics QE65Pro fiber optic spectrometer, and the data acquisition integration time is set to 600 milliseconds and the scanning step length is 1nm to ensure high-precision signal capture and resolution. The stress luminescent film will produce different luminous intensities when subjected to different mechanical loads. The experiment collects the stress luminescent spectrum signals of the film at each stage before and after the force, and judges the stress changes and stress concentration areas inside the bearing by analyzing the differences in these signals. This detection method based on the difference in stress luminescent signals helps to achieve non-destructive and real-time monitoring of the internal mechanical state of the bearing, and provides an effective means for health management and fault prediction of complex mechanical systems.

[0037] Example 2

[0038] SrAl2O4:Eu2+,Dy3+ stress luminescent powder and polydimethylsiloxane were selected as the starting compound raw materials, and the mass ratio of each compound was M1:M2=2:10. After the mixture was stirred and mixed, it was poured into a mold and placed in an oven. The heating rate was accurately controlled, and the samples were cured at 80, 90, 100, and 120°C for 2h. The spectral properties of the stress luminescent film were similar to those of the ratio (2) in Example 1.

[0039] Example 3

[0040] SrAl2O4:Eu2+,Dy3+ stress luminescent powder and polydimethylsiloxane were selected as the starting compound raw materials, and the mass ratio of each compound was M1:M2=2:10. After stirring and mixing, the mixture was poured into a mold and placed in an oven. The heating rate was accurately controlled, and the sample was cured at 80°C for 1, 2, 3, and 4 hours. The spectral properties of the stress luminescent film were similar to those of the ratio (2) in Example 1.

[0041] In particular, the stress luminescent film that records the stress information of a closed mechanical structure has the general formula: SrAl2O4:Eu2+,Dy3+ / polymer:M1 / M2; wherein 1≤M1≤3, 5≤M2≤15, Eu replaces Sr in the crystal; and the activation ion is Eu2+.

[0042] The method for producing a stress luminescent film for recording stress information of a closed mechanical structure comprises the following steps:

[0043] (1) The general formula is SrAl2O4:Eu2+,Dy3+ / polymer, and the mass ratio of the compounds shown is M1:M2; wherein 1≤M1≤3, 5≤M2≤15; the stress luminescent powder and the polymer raw material are weighed respectively according to the mass ratio.

[0044] (2) The compound raw materials weighed in step (1) are stirred and mixed, poured into a mold, and cured at low temperature, the temperature being 80-120°C.

[0045] (3) Curing the mixture in step (2) at 80-120° C. for 1-4 h in a curing environment to obtain a stress luminescent film with a low threshold value for recording stress information of a closed mechanical structure.

[0046] The temperature of the low temperature treatment is 80°C.

[0047] The treatment time is 2 hours.

[0048] The curing environment is vacuum.

[0049] The polymer-containing compound raw material is one or more of polydimethylsiloxane, polyurethane, polytetrafluoroethylene and polylactic acid.

[0050] The M1:M2 is preferably 2:10; the low-temperature curing temperature is preferably 80°C, and the curing time is preferably 2h for the best luminous effect.

[0051] The stress luminescent material of the present invention is an elastic stress luminescent film.

[0052] The principle of the present invention is as follows: Based on the mechanical stress-induced luminescent center excitation mechanism: when the film is subjected to external mechanical stimulation (compression), the external mechanical energy is effectively converted and transmitted to the stress luminescent powder dispersed in the polydimethylsiloxane matrix, thereby causing the energy level transition of the luminescent center (Eu2+), releasing photons and emitting light. The polydimethylsiloxane matrix provides excellent flexibility and toughness, allowing the film to maintain a stable structure and luminescent performance under repeated mechanical action.

[0053] The stress luminescent film of the present invention can realize stress luminescence at a low threshold, and its stress luminescence intensity can be self-recovered. The stress luminescent film of the present invention has the advantages of simple preparation conditions, batch production, and stable chemical properties, and can be applied to stress sensors, stress distribution imaging and other fields.

[0054] In particular, the present invention uses commercial stress luminescent powder SrAl2O4:Eu2+,Dy3+ and cheap polydimethylsiloxane as the matrix, and does not use harsh preparation conditions. The low-threshold stress luminescent film obtained is convenient for industrial mass production; compared with other existing elastic stress luminescent films, the SrAl2O4:Eu2+,Dy3+ / polydimethylsiloxane composite stress luminescent film has unique advantages. It does not require pre-irradiation treatment with high-energy rays, and can achieve spontaneous recovery of luminescence intensity under natural light or sunlight. After multiple stress luminescence cycles, the material can still maintain a stable and significant luminescence intensity, showing excellent stress luminescence durability and cycle stability. This feature makes it unnecessary to have additional pretreatment steps in practical applications, thereby reducing operational complexity and cost, and providing an efficient and convenient material selection for reusable stress luminescent closed mechanical stress monitoring.

[0055] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A stress luminescent film for recording stress information of a closed mechanical structure, characterized in that: The general expression formula is: SrAl2O4:Eu2+,Dy3+ / PDMS:M1 / M2; where 1≤M1≤3, 5≤M2≤15, Eu replaces Sr in the crystal; the activating ion is Eu2+.

2. The stress luminescent film for recording the stress information of a closed mechanical structure according to claim 1, characterized in that: The film does not require a high threshold to achieve stress luminescence, and its stress luminescence intensity can self-recover.

3. The stress luminescent film for recording the stress information of a closed mechanical structure according to claim 1, characterized in that: The preparation method of the stress luminescent film comprises the following steps: (1) The general formula is SrAl2O4:Eu2+,Dy3+ / polymer, and the mass ratio of the compounds shown is M1:M2, where 1≤M1≤3, 5≤M2≤15; weigh the compound raw materials of SrAl2O4:Eu2+,Dy3+ phosphor and polymer respectively according to the mass ratio; (2) The compound raw materials weighed in step (1) are stirred and mixed, and then poured into a mold, and cured at 70° C.-120° C. in a vacuum oven to obtain a low-threshold and self-recoverable stress-emitting luminescent film.

4. The method for preparing the stress luminescent film for recording the stress information of a closed mechanical structure according to claim 3, characterized in that: The M1:M2 is 2:

10.

5. The method for preparing the stress luminescent film for recording the stress information of a closed mechanical structure according to claim 4, characterized in that: The temperature for high temperature curing is 80-90°C.

6. The method for preparing the stress luminescent film for recording the stress information of a closed mechanical structure according to claim 5, characterized in that: The high temperature curing time in step (2) is 0.5-4h.

7. The method for preparing a stress luminescent material that does not require pre-irradiation and has instant luminescence self-recovery according to claim 6, characterized in that: The high temperature curing time is 2 hours.

8. The method for preparing the stress luminescent film for recording the stress information of a closed mechanical structure according to claim 3, characterized in that: The polymer raw material in step (1) is one or more of polydimethylsiloxane, polyurethane, polytetrafluoroethylene and polylactic acid.

9. A stress luminescent film and preparation method for recording stress information of a closed mechanical structure according to preparation method 3, characterized in that: The stress luminescent material is used in the fields of display and stress sensor and is used for monitoring the stress distribution of closed machinery.

Citation Information

Cited By

  • Stress distribution delay imaging film and preparation method and application thereof

    CN120574424A